WACANA ISLAM DALAM PERSPEKTIF KESEJARAHAN - Hoetoro, Arif (Jurnal Bestari, 1994)
Exploring the treaties upon the tradition of Islamic thought, Moslem Historians agree with each other to start the period of Ustman r.a.'s leadership as a the third  caliph replacing Umar r.a: This is considered as the culmination of trigger of scism origins that, in the long run, causes the four big mazhabs in Islam appear.